2006
DOI: 10.1021/tx0601206
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of p53 Mutations Induced by PAH o-Quinones with Those Caused by anti-Benzo[a]pyrene Diol Epoxide in Vitro:  Role of Reactive Oxygen and Biological Selection

Abstract: Polycyclic aromatic hydrocarbons (PAH) are one of the major carcinogens in tobacco smoke. They are metabolically activated through different routes to form either diol-epoxides, PAH o-quinones, or radical cations and each of which has been proposed to be an ultimate carcinogen. To study how PAH metabolites mutate p53, we used a yeast reporter gene assay based on the p53 transcriptional activity. Colonies expressing wt p53 turn white (ADE +) and those expressing mutant p53 turn red (ADE −). We examined the muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 46 publications
3
49
0
Order By: Relevance
“…Puisieux et al [39] were the first to show the direct role of PAHs in the development of mutations in the p53 gene in lung cancer. Shen et al [40] reported p53 mutation due to the formation of PAH o-quinones, one of the major carcinogens of PAHs, in cigarette smokers. It was suggested that PAH o-quinones cause p53 inactivation by generating endogenous reactive oxygen species [41].…”
Section: Discussionmentioning
confidence: 99%
“…Puisieux et al [39] were the first to show the direct role of PAHs in the development of mutations in the p53 gene in lung cancer. Shen et al [40] reported p53 mutation due to the formation of PAH o-quinones, one of the major carcinogens of PAHs, in cigarette smokers. It was suggested that PAH o-quinones cause p53 inactivation by generating endogenous reactive oxygen species [41].…”
Section: Discussionmentioning
confidence: 99%
“…Benz[a]anthracene-3,4-dione was a poor directacting mutagen in a yeast reporter-gene assay that detects p53 mutations. In the same assay, it was highly mutagenic under redox-cycling conditions in the presence of copper chloride and NADPH: single point mutations were observed, and the mutation pattern showed a high preference (>42%) for the formation of G→T transversions (Field et al, 2005;Shen et al, 2006).…”
Section: Cytotoxicitymentioning
confidence: 99%
“…2 As a rich source of chemical carcinogens and reactive oxygen species it can induce direct DNA damage and contribute to pathogenesis in urothelial cells. [3][4][5][6] The relationship between indirect DNA changes by epigenetics and tobacco smoke is to date not well understood.…”
Section: Introductionmentioning
confidence: 99%